2020
DOI: 10.1108/jsbed-01-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of cloud ERP in the SME: evidence from UAE

Abstract: PurposeThis study aims to explain the implementation of Cloud enterprise resource planning (ERP) system and underlying factors and challenges that might be practiced by the users. It also provides a comparison between traditional and Cloud ERP systems.Design/methodology/approachThe study uses qualitative case study and analyzes the primary evidences from in-depth interviews. It conducts a thematic analysis of the interviews' findings. Furthermore, the current study uses three groups of factors (technological, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 95 publications
1
51
0
Order By: Relevance
“…According to INT theory and in line with previous research of ERP adoption in the context of SMEs, it has been found that governmental policies act as an environmental pressure or driving force that is positively and significantly related to ERP adoption in SMEs, in an equivalent manner to CP in INT theory [60]. In addition, governments set related regulations (policies) that cover a diverse set of promotion programs or rules to pursue ERP system adoption/usage, which leads to the institutionalized adoption/use of ERP [46].…”
Section: Coercive Pressure and Erp Adoptionsupporting
confidence: 66%
“…According to INT theory and in line with previous research of ERP adoption in the context of SMEs, it has been found that governmental policies act as an environmental pressure or driving force that is positively and significantly related to ERP adoption in SMEs, in an equivalent manner to CP in INT theory [60]. In addition, governments set related regulations (policies) that cover a diverse set of promotion programs or rules to pursue ERP system adoption/usage, which leads to the institutionalized adoption/use of ERP [46].…”
Section: Coercive Pressure and Erp Adoptionsupporting
confidence: 66%
“…The theory asserts that opportunities and threats presented to a firm through these contexts trigger the need to diffuse technology or otherwise. Accordingly, several studies find consistency with the theory (Alsharari et al, 2020;Hiran & Henten, 2020;Ismail et al, 2017). These suggest that the diffusion of technology in SMEs could be affected by the quality of the human resource, the characteristics of the business, and the qualities of technology in question.…”
Section: Technology Acceptance Theoriesmentioning
confidence: 52%
“…They mainly focus on investigating whether there are significant relationships among CSFs for successful implementation rather than discussing the strength of sufficiency as well as criticality (strong, weak) of those CSFs. Failure to solve the importance of CSFs adequately may lead to the failure or less than desired results [28].…”
Section: Criticality and Attributes Of Csfsmentioning
confidence: 99%